2012
DOI: 10.4093/dmj.2012.36.2.157
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Opium Abuse and Severity of Depression in Type 2 Diabetic Patients

Abstract: BackgroundOpium use in diabetic populations is associated with major depressive disorder (MDD). This study was designed to investigate the relationship between opium use and severity of depression in Iranian diabetic patients.MethodsIn this case-control study, 642 type 2 diabetic patients were recruited from those presenting at two outpatient clinics at the Akhavan Hospital in Kashan, Iran; of them, 600 diabetic patients were included in the study and divided into two groups: opium-abusers (150 patients) and n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 32 publications
1
1
0
Order By: Relevance
“…21,22 Depressive symptoms are frequent in patients with comorbid conditions. [53][54][55][56] Consistent with previous research findings, 56,57 we found that patients with history of stroke were more likely to report a high level of depressive symptoms than those who had not had a stroke. Contrary to prior studies, 53,55,58,59 we found no association between history of myocardial infarction, hypertension, or diabetes mellitus and level of depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…21,22 Depressive symptoms are frequent in patients with comorbid conditions. [53][54][55][56] Consistent with previous research findings, 56,57 we found that patients with history of stroke were more likely to report a high level of depressive symptoms than those who had not had a stroke. Contrary to prior studies, 53,55,58,59 we found no association between history of myocardial infarction, hypertension, or diabetes mellitus and level of depressive symptoms.…”
Section: Discussionsupporting
confidence: 89%
“…In terms of the association between opium use and depression, Semenkovich et al [41] reported that there was a strong association between opium use and the development of depression. A study in Iran also clearly demonstrated that opium use significantly increased the incidence of severe depression [42]. Most hill tribe villages are located along the borders between Thailand, Myanmar and Laos, which are defined as the area that produces the most drugs in the world, making different drugs, such as amphetamine [12,43], opium [44], and heroin [44], readily accessible.…”
Section: Discussionmentioning
confidence: 99%